Role of Solvent in Electron‐Phonon Relaxation Dynamics in Core‐Shell Au−SiO2 Nanoparticles. Issue 21 (2nd September 2021) - Gogoi, Hemen; Maddala, Bala Gopal; Ali, Fariyad; Datta, Anindya
Abstract: Relaxation dynamics of plasmons in Au−SiO2 core‐shell nanoparticles have been followed by femtosecond pump‐probe technique. The effect of excitation pump energy and surrounding medium on the time constants associated with the hot electron relaxation has been elucidated. A gradual increase in the electron‐phonon relaxation time with pump energy is observed and can be attributed to the higher perturbation of the electron distribution in AuNPs at higher pump energy. Variation in time constants for the electron‐phonon relaxation in different solvents is rationalized on the basis of their thermal conductivities, which govern the rate of dissipation of heat of photoexcited electrons in the nanoparticles. On the other hand, phonon‐phonon relaxation is found to be much less effective than electron‐phonon relaxation for the dissipation of energy of the excited electron and the time constants associated with it remain unaffected by thermal conductivity of the solvent. Abstract : Environment effect on electron‐phonon relaxation dynamics : Higher thermal conductivity of the solvent leads to faster dissipation of accumulated heat in the core‐shell Au−SiO2 nanoparticles, resulting in smaller time constant associated with the relaxation of excited hot electrons.